Investigation of heat transfer in mechanical draft wet cooling towers using infrared thermal images: An experimental study. (April 2018) - Rahmati, Mehdi; Alavi, Seyed Rashid; Tavakoli, Mohammad Reza
Highlights: Influences of input parameters on the cooling tower performance are investigated. The temperature distribution is visualized by using captured thermal images. Thermal images are utilized to obtain temperature distribution along two directions. Regression analysis is employed so as to develop design equations. Some practical procedures are suggested to reach a better performance. Abstract: This article deals with an experimental investigation of thermal performance of mechanical draft wet cooling towers by changing various parameters such as hot water temperature, water flow rate, air mass flow rate and stage numbers of packing. In fact, this research attempts to focus on packing density influences with an emphasis on the role of stage numbers of packing. The results imply that coefficient of efficiency is in direct relation with air mass flow rate, hot water temperature and stage numbers of packing, while it diminishes by increasing the water flow rate. On the other hand, thermal images are provided for visualizing temperature distribution within the studied cooling tower. Afterward, these images are utilized so as to obtain pertinent temperature histograms and also temperature distribution along the vertical and horizontal directions for three packings. Finally, regression analysis is employed in order to derive design equations from the measured data.